The Influence of Blended Learning Model Based on Problems of Physical Learning Achievements by Students of Class X Science in SMA 6 Denpasar Academic Year 2017/2018 - Ni Putu Nadia Nikki Utami; I Wayan Santyasa; Iwan Suswandi (Universitas Ahmad Dahlan, 2018)
Learning achievement is the result achieved by someone after doing the learning process. One of the factors that influence learning achievement is the use of the learning model. This study aims to know the differences in achievement of students learning to use problem-based blended learning models and traditional blended learning. This study uses a quasi-experimental method of non-equivalent pretest-posttest control group design. The study population is all class X IPA with a total of 6 classes or 210 people. The sample consists of 3 classes or 107 people. Student learning achievement data were analyzed by descriptive analysis and ANOVA one-way (α = 0.05). The results of this study reveal that there are differences in student achievement due to the learning model. Higher learning achievement was achieved by problem-based blended learning models (F = 264.307; α<0.05). The LSD test results showed that the learning achievement of students in the MBLBM group was higher than MBL, the learning achievement of the MBLBM group was higher than that of MPK, and the learning achievement of the MBLBM group was higher than that of MPK.